2018
DOI: 10.1007/s10903-018-0776-8
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Recruiting African-Born, US-Based Participants for HIV and Tuberculosis Research

Abstract: Research is critical for developing HIV and tuberculosis (TB) programming for U.S. African-born communities, and depends on successful recruitment of African-born people. From January 2014 to June 2016, we recruited African-born people for HIV and TB research in King County, Washington. We compared the characteristics of study participants and the underlying populations of interest, and assessed recruitment strategies. Target enrollment for the HIV study was 167 participants; 51 participants (31%) were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Furthermore, the use of community networks, as well as of a strategy to identify the research team during events, gave the team visibility and reinforced a sense of trust in the community. Building relationships of trust with community members is vital to increasing participant recruitment [ 9 11 ]. The research team adopted a collaborative approach and established reciprocal relationships with community members (religious leaders, business people, and the leadership of community organizations).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the use of community networks, as well as of a strategy to identify the research team during events, gave the team visibility and reinforced a sense of trust in the community. Building relationships of trust with community members is vital to increasing participant recruitment [ 9 11 ]. The research team adopted a collaborative approach and established reciprocal relationships with community members (religious leaders, business people, and the leadership of community organizations).…”
Section: Resultsmentioning
confidence: 99%
“…African immigrants tend to be underrepresented in national health surveys (i.e., the Canadian Community Health Survey) leading to a gap in understanding the health needs of African immigrant women in Canada [ 6 – 8 ]. This is in part due to the challenges associated with engaging African immigrants in research; investigators conducting research with African immigrants, and other immigrant groups, often encounter substantial challenges in recruiting and gaining the trust of participants [ 9 , 10 ]. Even with the development and implementation of some innovative research approaches (i.e., community partnerships, involving community members in the research process, direct contact between participants and the research team at events) by health researchers to improve recruitment and retention of immigrant populations in Canada [ 10 , 11 ], we do not know if these strategies are effective in the recruitment of African immigrant women with infants.…”
Section: Introduction and Purposementioning
confidence: 99%
“…An additional finding was that non-Hispanic Black respondents had elevated perceptions of risk (compared to non-Hispanic Whites) when studies did not offer any payment. This is likely due to higher perceived risks of HIV research participation among Black individuals in general, driven by both (a) the historical targeted exploitation of African Americans in health research that has led to high levels of medical mistrust in doctors and researchers today, and (b) elevated levels of HIV-related stigma in some African American communities that would make any breaches of participant confidentiality socially costly [ 39 , 40 ]. Finally, regional variation existed in both perceptions of risk based on payment level and tolerance for the risk of potential harm incurred by research participation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, KII participants included somewhat fewer PLWH than we had anticipated recruiting, and the start of the COVID pandemic added complexity to recruitment for in-person interviews. We have previously found that African immigrant PLWH are less likely to agree to participate in research than members of other groups, likely related in part to fears around privacy and confidentiality [ 50 ]. Notwithstanding these limitations, our work is the most detailed and involving of the Ethiopian, Somali, and Eritrean communities around HIV-related and intersectional stigmas to date.…”
Section: Discussionmentioning
confidence: 99%